Legal concepts of running an agricultural holding as an individual - Łobos-Kotowska, Dorota (Przegląd Prawa Rolnego, 2021)
The issues discussed in the article concern the notion of running an agricultural holding in person. This term has been used for the purpose of restrictions in the trading in agricultural land contained in the Act on shaping the agricultural system. The requirement of “personal running” of an agricultural holding is extremely restrictive and gives rise to a number of doubts, including constitutional ones, which have been examined in the doctrine and in courts. Moreover, it seems to be a disproportionate interference in the way agricultural ownership is exercised, as well as in economic activity, including agricultural-economic. Any restriction of economic freedom and ownership rights should be considered through the prism of the proportionality principle. In order to ensure the fulfilment of the objectives of the Act on shaping the agricultural system, i.e. the proper management of agricultural land, it would seem to be sufficient to provide for an obligation to maintain the agricultural character of the real estate, with the implementation of the principle the latter is an area naturally maintained in a condition suitable for grazing or cultivation, with minimum standards being observed. Such an approach corresponds to the model of agriculture adopted in the Common Agricultural Policy.